Welfare schemes and social protection in India. Issue 3 (8th April 2014) - Jha, Raghbendra
Abstract : Purpose: – The purpose of this paper is to provide a broad overview of welfare schemes in India and their impact on social protection during a period of high economic growth. It summarizes India's performance with respect to select economic and social indicators relative to select low and middle-income countries in the Asia Pacific region. It further overviews trends in some key select economic and social indicators for India and discusses India's attainment in Social Protection relative to an index of such protection provided by the Asian Development Bank. Design/methodology/approach: – This paper uses a comparative statistical approach and evaluates India's performance in key social welfare areas vis-à-vis that of countries with economic performance comparable to that of India. It also evaluates India's progress along these parameters over time. Findings: – The basic messages of this paper are: first, compared to low and middle-income countries in the Asia Pacific India's economic performance has outstripped its performance in social and welfare indicators. Second, nevertheless India is spending less on social welfare programs and other welfare schemes than many countries in the Asia Pacific, including some of those whose economic performance has been less impressive than India's. Third, the efficiency and effectiveness of key welfare programs in India need to be substantially improved. Particular attention needs to be paid to female participation in and their access to social welfare programs. Originality/value: – Informed analyses of social sector spending in India and their impact on welfare outcomes are relatively scarce although descriptive studies of social sector spending and welfare schemes abound. This paper attempts to fill this gap with a cross-country as well as intertemporal analysis of India's performance in these key areas.